Amy Van Dyken's Full Arm Actions at 35 m of Her 50 m Gold Medal Race at the 1998 Perth World Championships - Rushall, B. S.
Video pictures (16 frames) and the appropriate technical/ biomechanical explanations for Amy Van Dyken's Full Arm Actions at 35 m of Her 50 m Gold Medal Race at the 1998 Perth World Championships. Amy Van Dyken displays an arm-stroking pattern that produces large and relatively continuous propulsive forces. It would seem that the left arm pull has better movement characteristics than the right arm. It would be interesting to see what performance changes would eventuate if the right arm kinematics were more direct than that exhibited here. It would seem that the left-arm pulling pattern is one worthy of emulation by female sprinters.